2018
DOI: 10.15244/pjoes/76910
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Digestion of Microalgal Biomass Acutodesmus dimorphus (Turpin) P. Tsarenko as a Substrate for Biogas Production

Abstract: It is only a matter of time for when fossil fuels will not be accessible at low cost, which is the major reason why it is obligatory for researchers to find an alternative feedstock to replace the currently stable position of fossil fuels in the world. The objective of this study was to review the potential of green microalgae Acutodesmus dimorphus (Turpin) P. Tsarenko, which can become the replacement for the commonly used raw materials for anaerobic digestion. Recent scientific focus has targeted the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The research has revealed elevated methane yield (0Á9143 m 3 kg À1 dry matters (DM)) in the AD of Acutodesmus dimorphus (Turpin) P. Tsarenko is an alternative resource due to their photosynthetic efficiency. In addition to the various potentials of AD, the digesters release CO 2 , which could cultivate microalgae (Głowacka et al 2018).…”
Section: Biogas Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research has revealed elevated methane yield (0Á9143 m 3 kg À1 dry matters (DM)) in the AD of Acutodesmus dimorphus (Turpin) P. Tsarenko is an alternative resource due to their photosynthetic efficiency. In addition to the various potentials of AD, the digesters release CO 2 , which could cultivate microalgae (Głowacka et al 2018).…”
Section: Biogas Productionmentioning
confidence: 99%
“…In addition to the various potentials of AD, the digesters release CO 2 , which could cultivate microalgae (Głowacka et al . 2018).…”
Section: Biogas Productionmentioning
confidence: 99%
“…The need to dispose of this biomass and wastewater treatment sludge on the Caribbean coast, provides the opportunity for its energy harnessing via AD. Furthermore, according to Głowacka et al [48] which at the same time can be used as a raw material in the AD process. Studies agree that the success of the marine algae fuel industry depends on the energy balance of the processes, and so evaluations are required that along with identifying the viability of the implementation, also enable the commercialization of the biofuels generated [22,33].…”
Section: Mathematical Modeling Of Biomethane Generationmentioning
confidence: 99%
“…High-rate algae ponds (HRAP) are an efficient and inexpensive technology for algae biomass production, and in which a large quantity of wastewater can be treated [3]. Algae growth is considerably influenced by climatic conditions, particularly temperature [4][5]. Low temperature restrains algae photosynthetic activities and reduces algae growth, resulting in low purification efficiency.…”
Section: Introductionmentioning
confidence: 99%